HCV-targeted Antivirals: Current Status and Future Challenges - Gemma, Sandra; Brogi, Simone; Novellino, Ettore; Campiani, Giuseppe; Maga, Giovanni; Brindisi, Margherita; Butini, Stefania (Current Pharmaceutical Design, 2014)
Hepatitis C virus (HCV) is the major etiological agent of human non-A and non-B hepatitis, affecting more than 170 million people worldwide. While the current standard of care for the treatment of HCV infection is ribavirin in combination with interferon-α (IFN-α), this therapeutic regimen presents several drawbacks, mainly related to important and serious side effects, to resistance issues, and to the lack of efficacy for the treatment of specific viral genotypes. In 2011, the FDA approved two HCV-targeted antivirals, namely boceprevir and telaprevir. These two drugs inhibit the protease activity of the viral enzyme NS3/4A, and in Phase III clinical trials proved to be effective in achieving sustained virological response rate up to 75%. However, problems associated with these therapeutic regimens still exist and need to be addressed. Intense research efforts in the field are aimed at discovering small-molecule inhibitors of HCV enzymes and proteins such as NS5B and NS5A and at developing NS3 protease inhibitors active against resistant viruses expressing mutated NS3 protease. The most recent advances for the rational drug design of such inhibitors are here reviewed.
Keywords: HCV